Migratory behaviour of tumour cells: a scanning electron microscopy study - Giuseppina Bozzuto; Maria Condello; Agnese Molinari (Istituto Superiore di Sanità, 2015)
BACKGROUND: Tumour cells utilize different migration strategies to invade surrounding tissues and elude anticancer treatments. It is therefore important to understand the mechanisms underlying migration process, in order to aid the development of therapies aimed at blocking the dissemination of cancer cells. AIMS: In this study tumour cell lines of different histological origin were analysed by combining 2D and 3D in vitro assays, biochemical tests and high resolution imaging by scanning electron microscopy (SEM) in order to look insight strategies adopted by tumour cells to invade extracellular matrix. RESULTS: Quantitative (computer-assisted colour camera equipped-light microscopy) and qualitative analysis (SEM) indicated that the most aggressive tumour cells adopt an "individual" behaviour. The analysis of intracellular signalling demonstrated that the highest invasive potential was associated with the activation of AKT, ERK, FAK and ERM proteins. The "individual" behaviour was positively related to the expression of VLA-2 and inversely related with the E-cadherin expression. CONCLUSIONS: The combination of 2D and 3D in vitro assays, biochemical tests and ultrastructural investigations proved to be a suitable test for the investigation of tumour cell migration and invasion. The high resolution imaging by SEM highlighted the interrelationships between cells in different migratory behaviours of tumour cells.